Effect of Positivism in Clinical Legal Education - FX Adji Samekto (The Indonesian Journal of International Clinical Legal Education, 2019)
Clinical Legal Education (CLE) is an education in legal study that aims to provide knowledge on practical expertise that aims to make law graduates capable of providing legal services (legal advocacy).CLE become important in recent days because of the tendency to resolve the matter through legal channels is increasing. But in fact, it shows that law enforcement is almost interpreted only as rule enforcement. The trend that happens, aspects of compliance procedures take precedence over justice. The modern law scientification is strongly influenced by the emergence of positivism paradigm in modern science. At present, along with the complexity of the problems of people and society, the main character of modern law is a rational nature. Rationality is characterized by the nature of a procedural rule of law. Procedure, thereby becoming an important legal basis to establish what is called justice, even the procedure becomes more important than talking about justice itself. Legal education, thus more likely to produce professional practitioners. The resulting legal practitioners are legal actors who are expected to make a decision which side is wrong and what is right under the provisions of the law. Through this paper is expected to obtain the understanding that CLE should not result the Law degree who only give priority to the compliance procedure as positive law, but also still guided ethics and efforts to achieve justice. The method used for writing this paper is the socio legal research with inductive analysis. Thus, the fact that occurred in the law enforcement practices will be a major premise and provide input and analysis in this paper.